Colonial Constitutionalism: The Tyranny of United States' Offshore Territorial Policy and Relations - Statham, Robert E., (Lexington Books, 2001)
Colonial Constitutionalism exposes one of the great failures of American democracy. It posits that the creation of a U.S. 'empire' over the last century violated the basis of American constitutionalism through its failure to fully admit annexed offshore territories into the Union. The book's focused case studies analyze each of America's quasi-colonies, revealing how the perpetuation of a this 'imperialist' strategy has rendered the inhabitants second class citizens. E. Robert Statham, Jr.'s work emphasizes the pressing need—in the face of increasingly strident calls for sovereign independence from America's offshore territories—for a modern American republic, fundamentally incompatible with imperialism and colonialism, to grant full U.S. statehood to its overseas possessions.